Bafilomycin A1 enhances NLRP3 inflammasome activation in human monocytes independent of lysosomal acidification. (21st November 2020) - Yu, Shi; Green, Jack; Wellens, Rose; Lopez‐Castejon, Gloria; Brough, David
Abstract : The release of interleukin (IL)‐1β from primary human monocytes in response to extracellular LPS occurs through the NACHT, LRR and PYD domains‐containing protein 3 (NLRP3) inflammasome. In primary monocytes, in response to LPS, NLRP3 inflammasome activation is characterized by an independence of K + efflux and ASC speck formation and has been termed the 'alternative' pathway. Here, we report that pharmacological inhibition of V‐ATPase with bafilomycin A1 exacerbated LPS‐induced NLRP3 inflammasome activation in primary human monocytes. Inhibition of V‐ATPase in the presence of extracellular LPS led to NLRP3‐dependent, K + efflux‐independent, ASC oligomerization and caspase‐1 activation. Although V‐ATPases are required for lysosomal acidification, we found that acidic lysosomal pH and protease activity were dispensable for this altered response, suggesting that V‐ATPase inhibition triggered alternative signalling events. Therefore, V‐ATPases may serve additional roles during NLRP3 inflammasome activation in primary human monocytes. Abstract : The NLRP3 inflammasome drives inflammation in response to tissue damage and infection by promoting the processing and release of IL‐1β. Human monocytes have an alternative pathway of NLRP3 inflammasome activation in response to lipopolysaccharide alone. Here, we report that the vacuolar ATPase, a lysosomal proton pump, is a regulator of the alternative NLRP3 response.